Reading and Writing Problem among B40 Students in Malay Language Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to identify the problems faced by among B40 students in reading and writing skills. This case study is conducted on 16 students from families that do not know B40 and substandard reading and writing in Malay Language. A total of 5 B40 Malay students, 7 B40 Chinese students and 4 B40 Indian students selected as study participants. All these students study in form 1 in two national secondary schools namely as SMKA and SMKB in Hulu Langat district, Kajang, Selangor. 8 B40 students from SMKA and 8 B40 students from SMKB. Structured interviews are used as a data collection tool. Interview data were analyzed narratively where the themes found were based on the analyzed transcripts. The findings of the study show that the main reading problem of B40 students is that they do not know how to read and do not understand what is being read. As for writing problems, B40 students do not know what is written. B40 Chinese students is the weakest students in reading and writing, followed by B40 Indian andB40 Malay students. Through the findings of this study, it can be concluded that the problem of reading and writing among B40 students is an issue that needs to be addressed by teachers, MOE and parents.